2017
DOI: 10.1038/s41598-017-04505-y
|View full text |Cite
|
Sign up to set email alerts
|

Effects of naftopidil on double-J stent-related discomfort: a multicenter, randomized, double-blinded, placebo-controlled study

Abstract: To evaluate the effect of naftopidil 75 mg once daily for ureteral double-J (DJ) stent-related discomfort after a ureteroscopic procedure using a multicenter, randomized, double-blinded, placebo-controlled study. 100 patients with indwelled retrograde DJ ureteral stents after ureteroscopic stone removal or retrograde intrarenal surgery (RIRS) were randomized 1:1 to receive either placebo or naftopidil during the stenting period. At the time of stent removal, the Ureteral Stent Symptom Questionnaire (USSQ), the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
13
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 14 publications
(15 citation statements)
references
References 30 publications
2
13
0
Order By: Relevance
“…The previous reports have demonstrated that ureteral stenting was clearly associated with worsening life quality and general health. Joshi et al have stated that 72% of patients were very dissatisfied and desperate after stent insertion but that rate decreases to 4% after stent removal (p Z 0.0001) [13]. In our study, the total USSQ score decreased after stent removal in groups 1 and 2.…”
Section: Discussionsupporting
confidence: 46%
“…The previous reports have demonstrated that ureteral stenting was clearly associated with worsening life quality and general health. Joshi et al have stated that 72% of patients were very dissatisfied and desperate after stent insertion but that rate decreases to 4% after stent removal (p Z 0.0001) [13]. In our study, the total USSQ score decreased after stent removal in groups 1 and 2.…”
Section: Discussionsupporting
confidence: 46%
“…The USSQ was developed to evaluate the discomfort associated with ureteric stents and it is currently widely used . The exact mechanism involved in ureteric stent‐associated discomfort is not yet known; however, many authors report that such discomfort is associated with ureteric spasms, urinary reflux attributable to ureteric stent, or trigonal irritation .…”
Section: Discussionmentioning
confidence: 99%
“…The USSQ was developed to evaluate the discomfort associated with ureteric stents and it is currently widely used [11]. The exact mechanism involved in ureteric stent-associated discomfort is not yet known; however, many authors report that such discomfort is associated with ureteric spasms, urinary reflux attributable to ureteric stent, or trigonal irritation [12]. Different novel types of stents have been developed and evaluated to reduce stent-related discomfort; however, there is still controversy regarding their clinical application [13].…”
Section: Discussionmentioning
confidence: 99%
“…To date, many studies have attempted to alleviate stent-related discomfort by agents, such as alpha-1 blockers, anticholinergics, and beta-3 adrenergic receptor agonists 13,[19][20][21][22] . These results regarding improvement of urinary symptoms are conflicting, and negative results have been found in several randomized, controlled trials 13,[20][21][22] . We believe that trials using medication should consider not only improvement of stent-related irritation, but also urinary symptoms that the patient has 23 .…”
Section: Discussionmentioning
confidence: 99%